2012
DOI: 10.1016/j.yjmcc.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Moderate ethanol ingestion and cardiovascular protection: From epidemiologic associations to cellular mechanisms

Abstract: While ethanol intake at high levels (3-4 or more drinks), either in acute (occasional binge drinking) or chronic (daily) settings, increases the risk for myocardial infarction and ischemic stroke, an inverse relationship between regular consumption of alcoholic beverages at light to moderate levels (1-2 drinks per day) and cardiovascular risk has been consistently noted in a large number of epidemiologic studies. Although initially attributed to polyphenolic antioxidants in red wine, subsequent work has establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
148
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 203 publications
(186 reference statements)
2
148
0
6
Order By: Relevance
“…The dietary questionnaire used in the GISSI-HF trial did not distinguish between red and white wine, 2 beverages whose content in biologically active compounds may differ, although the differences in the cardiovascular effects of the 2 kinds of wine have been questioned. 49 For this reason, data from GISSI-HF cannot be easily compared with other populations with different types and patterns of alcohol consumption. In addition, the design of the clinical trial did not permit any causal relationship but only associations between patient-reported wine consumption and health status, which may be influenced by unreported confounding clinical variables.…”
Section: Wine Consumption Qol and Depressionmentioning
confidence: 99%
“…The dietary questionnaire used in the GISSI-HF trial did not distinguish between red and white wine, 2 beverages whose content in biologically active compounds may differ, although the differences in the cardiovascular effects of the 2 kinds of wine have been questioned. 49 For this reason, data from GISSI-HF cannot be easily compared with other populations with different types and patterns of alcohol consumption. In addition, the design of the clinical trial did not permit any causal relationship but only associations between patient-reported wine consumption and health status, which may be influenced by unreported confounding clinical variables.…”
Section: Wine Consumption Qol and Depressionmentioning
confidence: 99%
“…In brief, alcohol in moderation favorably affects reverse cholesterol transport, insulin sensitivity, abdominal obesity, systemic inflammation and oxidative stress, endothelial function, endogenous fibrinolysis, postprandial hypercoagulability, and platelet aggregation. 3,[8][9][10][11][12][13] These effects are in part of reasonable size and may well contribute to the health benefits of habitual moderate alcohol consumption regarding coronary heart disease (decrease of 29%), 2 diabetes mellitus (decrease of 30% to 40%), 3 and life span (decrease of 17% to 18% in total mortality). …”
Section: Article See P 390mentioning
confidence: 99%
“…1,14 In small intervention trials and on the basis of pathophysiologic considerations, wine surpassed other types of alcoholic beverages in terms of favorable short-term metabolic changes. 3,9,11,12 To date, epidemiologic research has not confirmed the superiority of wine over spirits. 2 However, it must be remembered that, in epidemiologic work, it is challenging, if possible at all, to disentangle effects of different types of beverages in mixed drinkers, and drinking behaviors allocated to 1 type of beverage only are usually driven by cultural and regional peculiarities.…”
Section: The South Asian Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of EPT for CSA was not high in this study and we do not recommend this test for the screening and/or diagnosis of CSA. It is also to be noted that there may be some patients with CSA whose attack may be relieved by ingestion of small amounts of alcohol because small amounts of alcohol may enhance endothelial nitric oxide activity thereby leading to vasodilatation (25,26).…”
Section: Discussionmentioning
confidence: 99%